Correlation of Anti-Salmonella Antibodies Between Serum and Saliva Samples Collected From Finisher Pigs - De Lucia, Alessia; Cawthraw, Shaun; Davies, Rob; Smith, Richard P.; Bianco, Carlo; Ostanello, Fabio; Martelli, Francesca (Frontiers in Veterinary Science, 2020)
Saliva samples obtained by using absorptive devices, can provide an alternative diagnostic matrix to serum for monitoring disease status in pigs. The aim of this study was to investigate the correlation of anti-Salmonella antibodies between serum and saliva samples collected from pigs. Twenty individual paired serum and saliva samples were collected from a single farm. Anti-Salmonella IgG was detected in individual serum samples using a commercial Salmonella ELISA kit, validated for sera. The same kit was used with a protocol modified by extending incubation time and increasing temperature to test individual saliva samples. Anti-Salmonella IgG antibodies in pig saliva were always detected at a lower level than in the matching serum samples. A correlation (rho = 0.66; p = 0.002) and a moderate agreement (K > 0.62 p = 0.003) was found between individual Salmonella IgG in serum and saliva samples. Both correlation and the agreement levels are moderate. The size of this investigation was small, and further studies are necessary to further confirm these findings. The results of this work provide some evidence that saliva samples have the potential to be used for the diagnosis of Salmonella infection in pig farms.